Desvelando el acceso desigual al aprendizaje del inglés en las escuelas secundarias de la provincia de Copiapó - Torrico-Ávila, Elizabeth (2021)
In 2004, ‘Chile bilingüe’ marked the launch of a system  for teaching English in Chile. The goal of this language policy is to provide students with an intermediate profi ciency level upon graduation. Proficiency is measured by  the ‘SIMCE de inglés’ national test, with the results indica ting a gap between private and public sector institutions.  It is in this context that this article addresses this gap, fo cusing on the issue as revealed by the ‘SIMCE’ results in the  province of Copiapó, as well as offering suggestions on  how the gap could be narrowed. The methodology emplo yed to conduct this research is a multi-method approach,  involving surveys and archival studies. The results indica te a correlation between student numbers, resources and  teaching hours, and proficiency results among students. In  addition, teachers provide suggestions on how to address  the problem. The aim of this study is to suggest ways of  making English teaching more equitable, as well as encou raging further research on the topic.